2013
DOI: 10.1016/j.jcrysgro.2012.11.031
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive diagram to grow (0001)InGaN alloys by molecular beam epitaxy

Abstract: The composition, strain and surface morphology of (0001 )InGaN layers are investigated as a function of growth temperature (460-645 °C) and impinging In flux. Three different growth regimes: nitrogen-rich, metal-rich and intermediate metal-rich, are clearly identified and found to be in correlation with surface morphology and strain relaxation. Best epilayers' quality is obtained when growing under intermediate metal-rich conditions, with 1 -2 monolayers thick In ad-coverage. For a given In flux, the In incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…The as-received SiC substrates were prepared following the procedure described in Ref. 18 21 For all these samples, the nominal width of the barriers and the thickness of the final cap layer were 10.1 and 30 nm, respectively. The nominal width of the QWs was varied for each type of substrate between 2.6 and 12 nm.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…The as-received SiC substrates were prepared following the procedure described in Ref. 18 21 For all these samples, the nominal width of the barriers and the thickness of the final cap layer were 10.1 and 30 nm, respectively. The nominal width of the QWs was varied for each type of substrate between 2.6 and 12 nm.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…The In composition in InGaN layers depends critically on the growth temperature, 6,[16][17][18][19][20] being therefore necessary to establish a reference parameter that guarantees its reproducibility. For the PAMBE growth of GaN, the substrate temperature in the range of 700À750 C is calibrated by the Ga desorption time measured by RHEED.…”
Section: A Growth Parametersmentioning
confidence: 99%
“…PAMBE growth of InGaN has been reported following various approaches. Gacevic et al 6 presented a growth diagram of InGaN with In content up to 50% and identified an intermediate metal rich regime, with 1À2 monolayer (ML) thick In coverage, which provided best InGaN quality in terms of surface morphology. On the other hand, Yamaguchi et al 7 showed the growth of thick and uniform In x Ga 1-x N films with the entire alloy composition range (0.2 x 1) using the droplet elimination radical-beam irradiation method.…”
mentioning
confidence: 99%
“…It can be employed in order to take advantage of metastability, and to avoid phase separation, by exploiting low growth temperatures (T gr ) so that the mobility of indium atoms is reduced. 15 Due to the easier dissociation of In-N bonds, indium incorporation is favored at T gr < 500 C. 15,16 On the other hand, the surfactant effect of the indium adlayer formed under metal enrichment of the surface favors the desired two-dimensional (2D) growth. 17 Iliopoulos et al 18 have demonstrated PAMBE-growth of (0001) InGaN films over the entire composition range with high indium incorporation efficiency, using a low temperature range and almost stoichiometric flux ratios.…”
mentioning
confidence: 99%